2021
DOI: 10.3390/jcdd8030030
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Liver and Spleen Stiffness in Patients with Fontan Associated Liver Disease (FALD): A Case Series with Histopathologic Comparison

Abstract: The Fontan operation is the current surgical procedure to treat single-ventricle congenital heart disease, by splitting the systemic and pulmonary circulations and thus permitting lifespan to adulthood for the majority of newborns. However, emerging data are showing that Fontan-associated liver disease (FALD) is an increasing related cause of morbidity and mortality in patients with the Fontan circuit. We described the clinical, laboratory, and transient elastography (TE) findings in a case series of adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The sample was relatively small, due to the rarity of the disease, and we did not perform liver biopsy in our patients. However, MRE has been validated as an effective method to assess liver stiffness and prior research has indicated an association between hepatic stiffness and histological fibrosis in different diseases, including patients with Fontan [40,52,53]. Although we did not have age-matched controls; we could demonstrate increased myocardial and liver fibrosis in patients despite their younger age compared to controls.…”
Section: Discussionmentioning
confidence: 64%
“…The sample was relatively small, due to the rarity of the disease, and we did not perform liver biopsy in our patients. However, MRE has been validated as an effective method to assess liver stiffness and prior research has indicated an association between hepatic stiffness and histological fibrosis in different diseases, including patients with Fontan [40,52,53]. Although we did not have age-matched controls; we could demonstrate increased myocardial and liver fibrosis in patients despite their younger age compared to controls.…”
Section: Discussionmentioning
confidence: 64%
“… 19 Liver stiffness as determined by transient elastography correlates with the presence of fibrosis and allows for patient staging without the need for invasive biopsies 19 and for monitoring of FALD progression. 28 Murtuza et al 29 showed that patients with preserved ventricular function and moderate-to-severe liver fibrosis or VAST ≥ 2 were at higher risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the FALD is assuming a novel clinical entity, characterized by a condition influencing both the general state (i.e., fatigue, cyanosis, short-breath, intolerance to effort, poor growth, sarcopenia) and systemic organs function (i.e., heart, lungs, kidney, gut) and both the subject risk of complications related to liver disfunction (i.e., ascites, spontaneous peritonitis, hepatic-renal syndrome, hepatocellular carcinoma, GE varices bleeding and encephalopathy) or to failing Fontan (i.e., pulmonary hypertension, PLE, arrythmias, plastic bronchitis, reduced heart output, dots blood) that significantly compromises the patient's life expectancy [16,22].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this tool is not a standardized method, considering the congestive liver status in Fontan patients with possible overestimation of LS measurement [10,14]. Certain predictive scores based on serum markers were also developed for staging liver disease in different patient categories (i.e., with significant fibrosis or cirrhosis and with portal hypertension), but these models have been never applied or tested for FALD staging [15,16].…”
Section: Introductionmentioning
confidence: 99%